A prospective clinicopathological study on multinodular goiter in Iraqi patients - Mohammud Habash, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Background The thyroid gland is a shield considered to protect the larynx and plays very important functions in the body. Thyroid swellings and enlargement are commonly encountered in clinical findings and surgical practice. Thyroid enlargement with the formation of multiple distinct nodules is a characteristic of multinodular goiter (MNG). Iodine deficiency leads to an increase in the thyroid-stimulating hormone (TSH). Thus, prolonged stimulation by elevated TSH may develop MNG and be more prone to malignant transformation. Present study was planned to study clinicopathological aspect of MNG with respect to TSH hormone levels in Iraqi patientsMethod The present study was a hospital-based prospective study conducted in Al-Shafa Hospital, Diyala, Iraq, between January 2018 and January 2020. 41 patients aged between 15 and 75 years. Clinically diagnosed as multinodular goiter (MNG) were included in the study.Result In the present study, all the recruited patients are having swelling in the anterior side of the neck. The minimum age recorded in both genders was 22 years. While the maximum age in males was 60 years and in females it was 78 years, the total mean age was 45.5 years. Of the 40 patients, the majority of cases were female, that is, 34 patients, and the remaining 6 cases were male, having a sex ratio of female to male of 17:3. Total thyroidectomy was performed, and a histopathology study was carried out to check the malignancy. Inference In our study, we have found the pathological presentation of goiter is benign, and clinical swelling of the neck is observed. The majority of females were affected by MNG. Total thyroidectomy was the preferred method for the malignant cases over other types of surgeries.